2005
DOI: 10.1074/jbc.m411581200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Initiation Factor 2 of Trypanosoma brucei Binds Imported Formylated Elongator-type tRNAMet

Abstract: The mitochondrion of Trypanosoma brucei lacks tRNA genes. Its translation system therefore depends on the import of nucleus-encoded tRNAs. Thus, except for the cytosol-specific initiator tRNA Met , all trypanosomal tRNAs function in both the cytosol and the mitochondrion. The only tRNA Met present in T. brucei mitochondria is therefore the one which, in the cytosol, is involved in translation elongation. Mitochondrial translation initiation depends on an initiator tRNA Met carrying a formylated methionine. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…S1). Translation factors were distributed among ribosomal subunits as expected: initiation factor 2 (IF2) (Charriere et al, 2005) was detected exclusively in the small subunit, while elongation factor Tu (EF-Tu) was found in both small and large subunits (Table S1). The discrete sets of PPRs, including two repeat-containing proteins originally identified in the KPAP1 complex (Tb11.02.3180 and Tb927.8.3170, (Etheridge et al, 2008)), were enriched in either small or large ribosomal subunits (Tables S1 and S3).…”
Section: Resultssupporting
confidence: 56%
“…S1). Translation factors were distributed among ribosomal subunits as expected: initiation factor 2 (IF2) (Charriere et al, 2005) was detected exclusively in the small subunit, while elongation factor Tu (EF-Tu) was found in both small and large subunits (Table S1). The discrete sets of PPRs, including two repeat-containing proteins originally identified in the KPAP1 complex (Tb11.02.3180 and Tb927.8.3170, (Etheridge et al, 2008)), were enriched in either small or large ribosomal subunits (Tables S1 and S3).…”
Section: Resultssupporting
confidence: 56%
“…While not studied in Leishmania , methionyl-tRNA Met-e formylation appears essential for mitochondrial protein biosynthesis in the related trypanosomatid T. brucei [24]. Since both DHCH1 and FTL are located in the cytosol of L. major , and previous studies in T. brucei showed that the initiator methionyl-tRNA Met-e is formylated in the mitochondrial matrix [23], this implies that 10-CHO-THF can be transported across the mitochondrial membrane in trypanosomatids.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, following import into the mitochondrion, the cytosolic elongator tRNA Met-e acts as either an elongator tRNA Met , or is formylated and used as an initiator tRNA Met ; remarkably, the tRNA Met-i was not used in the trypanosome mitochondrion [23]. Lastly, methionyl-tRNA formylation is required for binding of the fMet-tRNA Met to initiation factor 2, and appears to be essential in trypanosomes [24]. In contrast, the requirement for initiator tRNA Met formylation appears highly variable in evolution; while initially considered essential in bacteria, later data suggested otherwise [25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable debate about the requirement for initiator Met-tRNA Met formylation, with genetic studies in both prokaryotes and eukaryotes yielding divergent conclusions – often within the same species [51]. RNAi (RNA interference) studies in trypanosomes showed little phenotype when targeting solely FMT , but strong growth inhibition when both FMT and IF2 were targeted simultaneously [52]. …”
Section: -Cho-thf: the Second Critical Form Of C1-folatementioning
confidence: 99%